Antimicrobial Brazilian Propolis (EPP-AF) Containing Biocellulose Membranes as Promising Biomaterial for Skin Wound Healing. (9th June 2013) - Barud, Hernane da Silva; de Araújo Júnior, Adalberto Miguel; Saska, Sybele; Mestieri, Letícia Boldrin; Campos, Juliana Alvares Duarte Bonini; de Freitas, Rubens Moreno; Ferreira, Nathália Ursoli; Nascimento, Andresa Piacezzi; Miguel, Felipe Galeti; Vaz, Mirela Mara de Oliveira Lima Leite; Barizon, Edna Aparecida; Marquele-Oliveira, Franciane; et al.
Abstract : Among remarkable discoveries concerning propolis, such as antifungal, antiviral, and antioxidant activities, its anti-inflammatory, and mainly its antibacterial, properties deserve special attention when skin wound healing is concerned. Based on this and knowing the distinctive performance of bacterial (BC) membranes on wound healing, in this work it is proposed to demonstrate the potent antimicrobial activity and wound healing properties of a novel propolis containing biocellulose membrane. The obtained propolis/BC membrane was able to adsorb propolis not only on the surface, but also in its interstices demonstrated by scanning electron microscopy, X-ray diffraction, Fourier transform infrared (FT-IR) spectroscopy, and thermogravidimetric assays. Additionally, the polyphenolic compounds determination and the prominent antibacterial activity in the membrane are demonstrated to be dose dependent, supporting the possibility of obtaining propolis/BC membranes at the desired concentrations, taking into consideration its application and its skin residence time. Finally, it could be suggested that propolis/BC membrane may favor tissue repair in less time and more effectively in contaminated wounds.